Suffixes Forming Nouns Found in the Novel the Art of Racing in the Rain by Garth Stein - I Komang Sulatra; Ni Nyoman Widiadnyani (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
The aims of this study are to find out the suffixes forming nouns from verbs used in the novel The Art of Racing in the Rain and analyze the process of those nominal suffixes. The data were taken from the novel The Art Racing in The Rain by Garth Stein. This research is descriptive qualitative research. The study combined two theories, those are the theory proposed by Katamba (1994), which was used to find out and classify the types of nouns derived from verbs, and the theory from McCarthy (2002), which is used to find out how the process of suffixation is found in the novel. The observation method was applied in collecting the data with several techniques, such as; reading and note-taking. Formal and informal methods were used in presenting the finding of this study. This study found 241 data which divided into six (6) suffixes. Those were 10 data of suffix -ation (4,1%), 18 data of suffix -er (7,5%), 125 data of suffix -ing (51,9%), 58 data of suffix -ion (24,1%), 29 data of suffix -ment (12,0%), and 1 data of suffix -ee (0,4%). Moreover, in this study, all those data were obtained in the process of the class-changing meaning of the word.